معدلات النمو السكانية في سورية بين التعدادات وسجل الأحوال المدنية وأثرها على تغير التراكيب العمرية والاحتياجات الغذائية للأسرة - حجازي, حسن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
شهد العالم خلال القرن الماضي زيادات في عدد السكان لم يسبق لها مثيل من قبل بسبب التقدم الطبي الذي استفادة منه الدول النامية وأدى إلى انخفاض معدل الوفيات وبقي معدل الولادات مرتفعاً، وسوريا كإحدى هذه الدول النامية شهدت زيادات سكانية كبيرة خلال الأربعين سنة الماضية حيث تضاعف عدد السكان أكثر من ثلاث مرات إلى أن ترسخت عوامل انخفاض معدلات الولادات وأخذ معدل النمو السكاني بالانخفاض، إلا أن الزيادة مازالت مستمرة بسبب اتساع شريحة النساء المنجبات نتيجة ذلك النمو المرتفع -على الرغم من انخفاض معدل الخصوبة الكلية (من 7 -3 مولود لكل امرأة)- وتقف حالياً على أعتاب المرحلة الثالثة من مراحل الانتقال الديموغرافي، ونتيجة لذلك تغيرت البنى التركيبية للسكان وبلغت نسبة من تقل أعمارهم عن 15 عاماً حوالي 48% من مجمل عدد السكان في عام 1981 وانخفضت إلى 37% في عام 2011، ومع ذلك تبقى مرتفعة وأدت إلى زيادة أعباء الإعالة التي ظهرت بوضوح خلال الأزمة التي نعيشها حالياً بسبب التضخم وارتفاع الأسعار وعجز كثير من الأسر عن توفير الاحتياجات الغذائية لأفرادها لعدم زيادة الدخول بما يتماشى مع التضخم واضطرار كل فرد من قوة العمل أن يعيل ثلاثة أفراد إضافة إلى نفسه. The world has witnessed during the last century, increases in the number of the population has never seen before because of medical advances that benefit from developing countries and led to a decline in the mortality rate remained the birth rate is high, and Syria as one of the developing countries saw large population increases over the past forty years, where the population has doubled more than three times that established lower birth rates and taking population growth and decline rate factors, but the increase is still going on because of the breadth of women slice Procreation a result of high growth - despite the low total fertility rate (from 3- 7 births per woman) - stands now on the threshold of the third stage of demographic transition, and as a result the structures of synthetic population changed and the percentage of those under the age of 15 years, about 48% of the total population in 1981 and decreased to 37% in 2011, however, it remains high and led to increased burdens dependency that emerged clearly during the crisis that we are living now because of inflation and rising prices and the inability of many families to provide for the nutritional needs of their members not to increase incomes in line with inflation and forced every member of the workforce has to support three people in addition to himself.